Mapa conceitual como ferramenta para o ensino das leis da termodinâmica - Jesus, Benedito Carlos de (2015)
The present work presents the results of a study done by graduate students and Bachelor of biological sciences UNEMAT-UNIVERSIDADE ESTADUAL DE MATO GROSSO, in the municipality of Cáceres-MT. The survey was conducted in the class 2014/2-full-time CAC690 with 27 students in the second half of 2014, being used the search context triad: Act of teaching – classroom context – assessment. In this triad suggests that the teacher in the Act of teaching, use conceptual maps as teaching tool to negotiate meanings. And within the context of the classroom, into which the previous knowledge that biology students have about entropy and through the concept map constructed by the students evaluate the evolution of the concepts studied. The strategy to be developed for the construction of concept maps involved the qualitative methodology, where the meaning that students give to the concepts of entropy and life are foci of attention and Special attention of the researcher, because this meant that in three specific steps that were built the conceptual maps could ascertain whether students rank, differentiated the main concepts of the secondary, related the concepts of entropy in thermodynamics and how they integrated the concepts of entropy, i.e. how they reconcile this concept integrativamente. Altogether there were seven steps (classes), being the first and the last to implement the tests, for subsequent comparison of the results. The results served to analyse and assess whether what was examined proved to be efficient and significant learning was reached.